Estimasi Biaya Pembangunan Perangkat Lunak Menggunakan Metode Use Case Point (Studi Kasus CV. Utomo Sakti (Cloud Astro Technology) ) - Budi Wasono; Widhy Hayuhardhika Nugraha Putra; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
CV. Utomo Sakti (Astro Cloud) is a software development company. In carrying out the project CV. Utomo Sakti (Astro Cloud) does not have a scientific method of estimating costs and time, and still use guessing method and experiences. In this study uses 4 project from CV. Utomo Sakti (Cloud Astro) in 2018 to become its object which is 2 is profile/portal website, and 2 of them is management information system type of project. From the calculating of the cost and time estimation result with Use case point method, then compared with the result of estimated cost and time from CV. Utomo Sakti (Cloud Astro) to find the average value of Percent error. For the work duration, it result a value 50.06% longer for the website, and 43.11% faster for the management information system. And then for project cost estimation result a value 8.33% more expensive for websites, and 33.33% more expensive for management information systems. After that, project schedulling is desribed by Gantt chart based on Work Breakdown Structure. The result of this study can later be considered for CV. Utomo Sakti (Astro Cloud) in estimating the cost of software projects.